Using the Sociodrama Method to Improve Students' Understanding of the Content of Dramatic Texts - Siti Lestari Sinta (Universitas Sebelas Maret, 2020)
Efforts to increase students' understanding of the content of drama texts are still experiencing obstacles, because they are still using the lecture method in learning. In this regard, it is necessary to carry out meaningful learning methods for students, namely how they are able to involve the activeness of students. The sociodrama method is a learning method by dramatizing human behavior, which involves interaction between two or more people about a theme. The purpose of writing this article is to describe the use of the sociodrama method to improve students' understanding of the content of drama texts. This article explains the meaning of learning, the benefits of learning Indonesian language material. Drama is part of the Indonesian language subject matter. This article also discusses the meaning of the sociodrama method, its objectives, roles, implementation steps, virtues, weaknesses and suggestions when using the sociodrama method. The sociodrama method can improve students' understanding of drama texts. The involvement of students playing drama texts trains students to understand the content of drama texts and understand the characters played.